ANALISIS LITERATUR TENTANG PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI DAN KINERJA PERUSAHAAN DI INDONESIA - Ridwan, Isnaini (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to review the literature from 26 scientific articles that examine the influence of Good Corporate Governance (GCG) mechanisms on company value and performance in Indonesia. GCG variables that are often analyzed include managerial ownership, institutional ownership, the existence of an independent board of commissioners, board of directors, and audit committee. Several studies also include moderator variables such as audit quality and mediating variables such as earnings management and financial performance (ROA). The majority of articles use multiple linear regression methods with purposive sampling techniques. The results of this review indicate that the impact of GCG on company value and performance is still diverse and inconsistent. However, institutional ownership and profitability variables more often show a significant positive influence on increasing company value. This study recommends the need for standardization of GCG indicators and encourages further research with a more comprehensive quantitative approach and considering the influence of other external factors.